The Short-Term Effect of Video Editing Pace on Children's Inhibition and N2 and P3 ERP Components during Visual Go/No-Go Task. Issue 4 (19th May 2019) - Kostyrka-Allchorne, Katarzyna; Cooper, Nicholas R.; Kennett, Steffan; Nestler, Steffen; Simpson, Andrew
ABSTRACT: We investigated the immediate consequences of differently paced videos on behaviour and neural activity during response inhibition. Forty 7-year-olds watched a fast- or slow-paced video and completed a go/no-go task. Compared to the slow-paced-video group, children in the fast-paced-video group made more no-go errors. There was also an interaction between pace and no-go response type (correct, wrong) for the N2 and P3 peak latencies. In the slow-paced group, both components peaked earlier for correct response withholds. This usual pattern of activation was absent in the fast-paced group. Video pace appears to affect behaviour and the neural responses involved in inhibition.